AB0475 Biologics in Monotherapy in rheumatoid Arthritis: A Multicentric Restrospective Study of 109 Patients. (9th June 2015) - Rahal, N.; Afif, N.; Ardizzone, M.; Sparsa, L.; Schaeffer, M.; Messer, L.; Moreau, P.; Sibilia, J.; Sordet, C.
Abstract : Background: According to the EULAR recommendations for the management of patients with rheumatoid arthritis (RA), the use of a biologic therapy should be done in combination with methotrexate (MTX) or another synthetic DMARD (csDMARD). However, in "real-life studies", 30% of the patients are treated with biologic in monotherapy. Objectives: Our objectives were to describe the characteristics of patients with RA receiving intravenous biologic therapy without csDMARD and the reasons for monotherapy. Methods: We made an observational, retrospective and multicentric study in 3 rheumatology units in Alsace (France) between the 1/01/13 and the 31/01/14. Patients with a RA diagnosis according to the 2010 ACR criteria and treated with abatacept (ABA), infliximab (IXF), rituximab (RTX) or tocilizumab (TCZ) with no MTX, sulfazalazine, leflunomid or hydroxychloroquine for at least 3 months were included. Collected variables included patients' characteristics (age, gender and comorbidities), RA characteristics, past and present antirheumatic therapies. Results: 109 (27%) patients treated with an intravenous biologic were in monotherapy; 74% were women, mean (SD) age was 65 (12) years. Mean time (SD) since RA diagnosis was 15.2 years (9.4). 78% had rheumatoid factor and 72% anti-CCP antibodies, 80% had joint damage. Among the 109 patients, 20 (18.3%) were treated with ABA, 8 (7.3%) with IFX, 48 (44%) with RTX and 33 (30.3%) with TCZ. The mean (SD) DAS28 at the treatment initiation was 5 (1.4). The mean DAS28 (SD) at the last cure was 3.4 (1.4). The mean (SD) dose of oral corticosteroid at the last cure was 7.4 mg/d (5.5). The biologic was initiated in combination with 30% of patients and in monotherapy with 70% of patients. Patients had received a mean (SD) of 2.2 (1) synthetic DMARDs and 2.46 (1.3) biologics. 94% of patients previously received MTX, 58% MTX and LFN and 11% the 4 csDMARDs. About MTX, 43 patients were treated orally (57%), 25 subcutaneously (33%) and 7 had the 2 routes (9.3%). The mean dose before stopping MTX was 13.8mg ±4.4. Reasons for stopping MTX were: intolerance for 73% of patients, lack of effectiveness for 10% of patients, patient refusal (4%) and cancer (3%). Among withdrawals for intolerance, there was 35% of gastro-intestinal intolerance (abdominal pain, diarrhea, dyspepsia, nausea, loss of appetite), 30% of liver intolerance (ASAT and/or ALAT elevation superior to 2N), 11% of hematological intolerance and 8% of lung intolerance. 7 patients never had MTX: 6 because of medical contraindication and 1 refused. Conclusions: Use of biologics in monotherapy is frequent though combination showed better control of disease progression and less immunogenicity. In our study, most patients previously received at least 2 csDMARDs. The most frequent reason for MTX withdrawal was gastrointestinal intolerance and only few patients received MTX in parenteral. In order to optimize the MTX, practitioners should give good information about side effects, try low dose of MTX, switch from oral to parenteral administration, assess the adherence to folic acid supplementation. Disclosure of Interest: None declared